Características de carcaça e qualidade da carne de cordeiros alimentados com silagem de palma e com ofertas intermitentes de água - Souza, Aelson Fernandes do Nascimento (2018)
This objective of this study to evaluate the effect of the different proportions of cactus pear silage (Opuntia fícus-indica mill) and the intermittent supply of water in sheep with no defined racial pattern on carcass characteristics and meat quality. This study used 36 male sheep, with no defined racial pattern were used, with a mean initial weight of 19.8 ± 2.1 kg and mean age of 6 months, distributed in a randomized complete block design in a 3 x 3, composed of 3 substitution proportions of tifton hay by palm silage in the diet (0, 21 and 42%) and three water supply intervals at the watering station (0, 24 and 48 hours) with 4 replicates during 84 days in feedlot. The intermittent supply of water influenced (P <0.05) only the morphometric measure of the croup width and the weight of the spleen organ. There was an effect (P <0.05) of the inclusion of cactus pear silage on the majority of biometric and morphometric means, with higher values corresponding to the treatments with 42% of cactus pear silage. The animals fed with cactus pear silage showed higher values for empty body weight, warm and cold carcass weight, carcass yield, lower cooling loss, with AOL (13.98) higher in the treatment containing 42% silage. The treatment without the inclusion of cactus pear silage presented lower weights of the commercial cuts, however, their yields were not affected. The animals that received 42% of cactus pear silage in the diet presented greater organ development and buchada weight (5.07 and 5.43). The tissue composition of the animals that received palm silage had higher muscle and bone weights. Less bright meat, with a lower red and yellow hue were verified with the inclusion of 42% silage. Some saturated, monounsaturated and polyunsaturated fatty acids were affected with a 42% inclusion of cactus pear silage in the diet. The intermittent supply of up to 48 hours does not affect the carcass characteristics and meat quality of lambs. The replacement of tifton hay in 42% of palm silage provides greater body development of lambs, heavier and higher yielding carcasses, higher weights for commercial cuts, meat with good quality and lipid profile of the meat with little expressive differences in relation to that of tifton hay.